Physical and mental fatigue reduce psychomotor vigilance in professional football players - Angius, L.; Merlini, M.; Hopker, J.; Bianchi, M.; Fois, F.; Piras, F.; Cugia, P.; Russell, J.; Marcora, S. M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Professional football players experience both physical and mental fatigue (MF). The main aims of this randomized crossover study were to investigate the effect of MF on repeated-sprint ability (RSA) and the effects of both physical fatigue and MF on psychomotor vigilance. Methods: Seventeen male professional football players performed 10 maximal 20-m shuttle sprints interspaced by incomplete recovery (RSA test). Running speed, heart rate, brain oxygenation, and rating of perceived exertion were monitored during each sprint. The RSA test was preceded by either a 30-minute Stroop task to induce MF or by watching a documentary for 30 minutes (control [CON]) in a randomized counterbalanced order. Participants performed a psychomotor vigilance test at baseline, after the cognitive task (MF or CON), and after the RSA test. Results: Heart rate and rating of perceived exertion significantly increased, while running speed and brain oxygenation significantly decreased over the repeated sprints (P < .001) with no significant differences between conditions. Response speed during the psychomotor vigilance test significantly declined after the Stroop task but not after CON (P = .001). Response speed during the psychomotor vigilance test declined after the RSA test in both conditions (P < .001) and remained lower in the MF condition compared to CON (P = .012). Conclusions: MF does not reduce RSA. However, the results of this study suggest that physical fatigue and MF have negative and cumulative effects on psychomotor vigilance. Therefore, strategies to reduce both physical fatigue and MF should be implemented in professional football players.